2018
DOI: 10.21037/jtd.2018.04.159
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of lung cancer with multiple lesions: implication of the new recommendations of the 8th edition of the TNM classification for lung cancer

Abstract: The 8 th tumour, node and metastasis (TNM) revision of the staging classification for lung cancer has attempted to clarify the different properties of four distinct clinical presentations: synchronous multiple primary lung cancers; primary tumour with intrapulmonary metastases; pneumonic-type adenocarcinoma and multiple ground glass/lepidic lesions. The respective biological profiles determine different surgical strategies for each category. Accurate preoperative histological confirmation is required to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Researchers believed that synchronous MPLC with ipsilateral sites should apply lung function preserving approaches, i.e. sublobar resection, while avoiding pneumonectomy; and those with contralateral sites should adopt staged operation [4]. Yet no evidence was given in terms of the sequence of resections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers believed that synchronous MPLC with ipsilateral sites should apply lung function preserving approaches, i.e. sublobar resection, while avoiding pneumonectomy; and those with contralateral sites should adopt staged operation [4]. Yet no evidence was given in terms of the sequence of resections.…”
Section: Discussionmentioning
confidence: 99%
“…At present, surgery is considered as the first choice of treatments for MPLC patients [4, 5] as few researches concerning other treatments were reported. Although there were some studies about surgical treatment of MPLC, it remains controversial about the prognosis of these patients and its impacting factors, such as different resection methods [6].…”
Section: Introductionmentioning
confidence: 99%
“…For multiple pulmonary nodules, segmentectomy can potentially reduce the loss of lung function even further. Waller et al [31] found that for multiple primary lung cancer types, segmentectomy is recommended, and lung resection should be avoided; segmentectomy can also allow for the ability to perform future lobectomies. Therefore, segmentectomy compared with lobectomy could have more advantages for the retention of lung function in the shortterm.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers believed that synchronous MPLC with ipsilateral sites should apply lung function preserving approaches, i.e. sublobar resection, while avoiding pneumonectomy; and those with contralateral sites should adopt staged operation [4].…”
Section: Discussionmentioning
confidence: 99%